Effect of Correlated Color Temperature of OLED Lighting on Near Work-induced Transient Myopia and Accommodation Lag during Reading - Bai, Weiling; Wei, Shifei; Gan, Jiahe; An, Wenzai; Liang, Xintong; Cai, Zhining; Sun, Yunyun; Li, Shi-Ming; Wang, Ningli (Ophthalmic research, 2025)
Purpose: To evaluate the effect of different correlated color temperatures (CCT) of organic light-emitting diode (OLED) lighting on accommodative lag (LAG) and near work-induced transient myopia (NITM). Methods: The refractions of 31 young adults (11 male) were measured with an open-field autorefractor at 33 cm after 30 and 60 minutes of reading under 4274 K and 1877 K. The initial NITM and LAG were assessed objectively at baseline and every 30 minutes. The use of two CCTs was determined in the order of the random number table. Results: After reading under for 30 minutes, the mean LAG for low-CCT lighting was slightly lower than the high-CCT lighting (-0.97 ± 0.53 D vs -1.21 ± 0.50 D, P = 0.10); after reading for 60 minutes, the difference was significant (-1.09 ± 0.55 D vs -1.36 ± 0.51 D, P = 0.048). When grouped according to the degree of myopia, both mild myopes (-1.11 ± 0.43 vs -1.38 ± 0.60 after 30-minute reading, P = 0.38; -1.34 ± 0.27 vs -1.5 ± 0.54 after 60-minute reading, P = 0.53) and moderate myopes (-0.90 ± 0.57 vs -1.12 ± 0.42 after 30-minute reading, P = 0.16; -0.96 ± 0.61 vs -1.28 ± 0.50 after 60-minute reading, P = 0.05) presented lower LAG magnitude under low-CCT lighting than high-CCT lighting, while the difference was not significant. As for NITM, no significant difference has been found between two CCTs in any group. Conclusion: Reading under low-CCT lighting (1877 K) had a lower LAG magnitude than reading under high-CCT lighting (4274 K), suggesting the potential usefulness of low-CCT lighting for reducing LAG magnitude during near work.